From tropicamp to tropicuir: writing histories from sex and gender dissident art (Palíndromo, 2022)
This article seeks to reflect on ways of writing dissident sex and gender histories through the arts, through a dialogue with several manuscripts of the artist Hélio Oticica and an experimental exercise on the term tropicuir, coined by me during my master's and doctoral studies, from which the present text derives. Based on queer and cuir theoretical reflections - including Foucault, Preciado, Rolnik and Gómez-Peña - I defend the hypothesis that insurgent aesthetic productions of gender and sex-dissident people act as generating machines of contranormative subjectivations that is, as networked micropolitical actions, counter-sexualities have been conforming collective memory of existences historically invisibilized in the shifting and violent Brazilian territory.
Keywords: Helio Oiticica; Gender and sexuality; Queer theory; Art history